Mental Health and Political Representation: A Roadmap - Bernardi, Luca (Frontiers in Political Science, 2021)
Research on health and political behaviour has identified a significant mental health-participation gap that is likely to have important consequences for political equality. Yet such consequences remain by and large unexplored. Inspired by 60 years of empirical research on public opinion, media and policy, this article proposes a roadmap for research on the political representation of mental health. It advances a number of research questions around (1) opinion formation and issue emergence and evolution, (2) multiple and complementary societal signals that can influence policy makers’ issue attention and policy change, and (3) different conceptions of representation and their consequences for public attitudes and political participation. The article also provides a preliminary attempt at addressing whether mental health spending incorporates signals from public preferences for spending on mental health services or policy problems. Making use of time-series data on spending on mental health services by local authorities in England between 1994 and 2013, the analysis finds no statistical association between spending and policy problems and reveals a negative relationship between spending and public preferences, suggesting that if spending is reacting at all to preferences, it misrepresents them. This article invites scholars to collect more data and produce more research that will guide interventions to help overcome stigma and participation challenges that undermine political equality as one of the key principles of democracy.